Sumbangan Sultan Omar (m. 1876) dalam Penulisan Manuskrip Quran Terengganu Pada Abad ke 19: Contribution of Sultan Omar (d. 1876) in Writing Terengganu Quran Manuscript in the 19th Century - Azmi, Riswadi; Abdullah, Mustaffa; Puteh, Mohd Nurudin; Awang, Zulkeefli; Izham, Siti Sarah; Md Ariffin, Mohd Farhan (Journal of Al-Tamaddun, 2022)
The writing of the Qur’an has started since it was revealed to the Prophet S.A.W in the seventh century AD. The effort to copy this sacred words was also done by the caliph al-Rashidin, especially Sayidina Uthman al’Affan until through various improvement processes to ensure that Muslims can use this scripture more easily and in accordance with the latest approach. There are a number of great Islamic empire has made an effort to copy the manuscripts of the Qur’an and this is also true in the Malay world. The Sultanate of Terengganu is recorded among the 11 Islamic sultans that have carried out this copying effort since the 18th century AD. The objective of this study is to identify the era of the Terengganu sultanate who carried out this noble endeavor as the Terengganu sultanate was founded in 1708 AD and ruled by 17 sultans until now. To ensure that the objectives of this study are achieved, qualitative research methods are used by looking at the evidence available in all Terengganu Qur’an manuscript and examining the colophon notes found in the manuscript. To support this study, historical records on the development of Islam and culture are also used as reference. The results of the study found that the Terengganu Quran manuscript has been actively produced during the era of the Baginda Sultan Omar. This is evidenced when four of the five manuscripts of the Qur’an have recorded the date of writing which occurred with the date of his reign. In addition, Baginda Sultan Omar is one of the longest-ruling sultans of Terengganu and and his contribution in knowledge and culture has been recorded in past historical records. The heritage of the Quran manuscript is proof that Baginda Sultan Omar was a ruler who always upheld Islam as the official religion of the state.